ISLAMIC MORAL VALUES IN A MOVIE "BILAL: A NEW BREED OF HERO" BASED ON AL-GHAZALI’S PERSPECTIVE - Fauzi, Ach; Rahmawati, Fithriyah (Islamuna: Jurnal Studi Islam, 2024)
This study aimed at analyzing the Islamic moral values in a movie entitled “Bilal: A New Breed of Hero” by using al-Ghazali’s theory of moral principal virtues. This study used a qualitative approach with library research as the kind of research. The primary source was “Bilal: A New Breed of Hero”, a movie produced by Barajoun Entertainment. While the secondary sources were articles, books, and theses related to this research to complete the primary data. In collecting the data, the researcher implemented observation and documentation. As a result, the Islamic moral values (moral principle values) found in Bilal: A New Breed of Hero movie were al-Hikmah (wisdom), as-Syaja’ah (courage), al-Iffah (temperance), and al-Adl (justice). The current research contributes greatly to disseminating moral values, especially from the Islamic perspective through the movie.